Morphine Efficacy, Tolerance, and Hypersensitivity Are Altered After Modulation of SUR1 Subtype KATP Channel Activity in Mice - Fisher, Cole; Johnson, Kayla; Okerman, Travis; Jurgenson, Taylor; Nickell, Austin; Salo, Erin; Moore, Madelyn; Doucette, Alexis; Bjork, James; Klein, Amanda H. (Frontiers in Neuroscience, 2019)
ATP-sensitive potassium (KATP) channels are found in the nervous system and are downstream targets of opioid receptors. KATP channel activity can effect morphine efficacy and may beneficial for relieving chronic pain in the peripheral and central nervous system. Unfortunately, the KATP channel exists as a heterooctomer, and the exact subtypes that are responsible for the contribution to chronic pain and opioid signaling in either dorsal root ganglia (DRG) or the spinal cord are yet unknown. Chronic opioid exposure (15 mg/kg morphine, s.c., twice daily) over five days produces significant downregulation of Kir6.2 and SUR1 in the spinal cord and DRG of mice. In vitro studies also conclude that potassium flux after KATP channel agonist stimulation is decreased in neuroblastoma cells treated with morphine for several days. Mice lacking the KATP channel SUR1 subunit have reduced opioid efficacy in mechanical paw withdrawal behavioral responses compared to wild-type and heterozygous littermates (5 and 15 mg/kg, s.c., morphine). Using either short hairpin RNA (shRNA) or SUR1 cre-lox strategies, downregulation of SUR1 subtype KATP channels in the spinal cord and dorsal root ganglia of mice potentiated the development of morphine tolerance and withdrawal. Opioid tolerance was attenuated with intraplantar injection of SUR1 agonists, such as diazoxide and NN-414 (100 uM, 10uL) compared to vehicle treated animals. These studies are an important first step in determining the role of KATP channel subunits in antinociception, opioid signaling, and the development of opioid tolerance, and shed light on the potential translational ability of KATP channel targeting pharmaceuticals and their possible future clinical utilization. These data suggest that increasing neuronal KATP channel activity in the peripheral nervous system may be a viable option to alleviate opioid tolerance and withdrawal